2014
DOI: 10.1037/a0037751
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal trajectories of social reticence with unfamiliar peers across early childhood.

Abstract: Behavioral inhibition is a temperament assessed in the toddler period via children’s responses to novel contexts, objects, and unfamiliar adults. Social reticence is observed as onlooking, unoccupied behavior in the presence of unfamiliar peers and is linked to earlier behavioral inhibition. In the current study, we assessed behavioral inhibition in a sample of 262 children at ages two and three, and then assessed social reticence in these same children as they interacted with an unfamiliar, same age, and same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
87
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(94 citation statements)
references
References 73 publications
6
87
0
Order By: Relevance
“…3 Over development, the stimuli that elicit distress in BI generally narrow to social contexts. 4 Consistent with this pattern, BI is predictive of social reticence in childhood 5 and remains one of the most robust predictors of later social anxiety. 6 However, the exact reasons why early childhood BI is linked to later social anxiety remain unclear.…”
Section: Introductionmentioning
confidence: 68%
“…3 Over development, the stimuli that elicit distress in BI generally narrow to social contexts. 4 Consistent with this pattern, BI is predictive of social reticence in childhood 5 and remains one of the most robust predictors of later social anxiety. 6 However, the exact reasons why early childhood BI is linked to later social anxiety remain unclear.…”
Section: Introductionmentioning
confidence: 68%
“…Alternatively, it is likely that the link between BI and anxiety may occur only among a subgroup of inhibited children or anxious children (Degnan & Fox, 2007). Specifically, previous research has shown that only a sub-group of inhibited children who continue to be socially reticent across childhood may be at-risk for developing anxiety problems (Chronis-Tuscano et al, 2009; Degnan et al, 2014; Degnan & Fox, 2007). In addition, the focus of most previous studies, in which the direct relation between BI and anxiety was reported, has been on children with social anxiety disorder (e.g., Chronis-Tuscano et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some studies have found no direct link between early childhood BI and later anxiety problems (Gladstone, Parker, Mitchell, Wilhelm, & Malhi, 2005; Biederman et al, 2001), particularly when BI is not sustained across early childhood (Degnan et al, 2014). These results suggest that some inhibited children may have buffers that protect them from internalizing problems, including anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…One such group is those who display higher levels of anxiouswithdrawal (AW), which is characterized by increased reticence and nervousness when in less familiar settings. While disengagement in social interactions can stem from a variety of factors, such as peer rejection, a preference for solitude, and developmental delays, which can be difficult to differentiate (Coplan, Ooi, Rose-Krasnor, & Nocita, 2014;Eisenberg, Shepard, Fabes, Murphy, & Guthrie, 1998;Rubin, Coplan, & Bowker, 2009), one prevailing theory is that young children most often display anxious withdrawal due to a combination of a more cautious/fearful disposition and exposure to an environment that is perceived as threatening in some way (Buss, 2011;Degnan, et al, 2014;Eisenberg et al, 1998;Gazelle, 2006). This early cautiousness has also been associated with development of social anxiety, which is largely characterized by a fear negative social appraisal (Clauss & Blackford, 2012;Coplan & Arbeau, 2008;Hirshfeld-Becker, 2007).…”
Section: Such As the Early Intervention Program For Infants And Toddlmentioning
confidence: 99%
“…This might present as quickly crying or freezing when in less familiar settings. Subsequently, these children have a higher risk for developing an anxiety disorder (Buss, 2011;Buss et al, 2013;Clauss & Blackford, 2012;Degnan et al, 2014;Hudson et al, 2011). For instance, in a sample of 146 preschoolers who displayed profound levels of behavioral inhibition, 90% met criteria for a diagnosable anxiety disorder (Rapee et al, 2005).…”
Section: Anxious-withdrawal In Young Childrenmentioning
confidence: 99%